MRI of stress reaction of the distal humerus in elite tennis players - Lee, J. C.; Malara, F. A.; Wood, T.; Hoy, G.; Saifuddin, A.; Connell, D. A. (American Journal of Roentgenology, 2006)
OBJECTIVE: The purpose of this study was to describe the MRI appearance of stress reaction in the distal humerus in 12 elite tennis players. In addition, we aimed to determine whether any MRI findings were associated with changes in recovery times.